Infl uence of Empowerment on Learning Achievements in students of the Faculty of Mathematical Sciences - Peña Miranda, Carlos Alberto (2019)
Empowerment influences learning achievements in a sample of female students from the four schools that make up the Faculty of Mathematical Sciences of the National University of San Marcos. A causal correlational design was used, with a sample of 200 students, to whom the empowerment inventory of Hernández, J. and García, R. was applied, and for the learning achievements were taken as data, the final grades obtained in the academic semester 2017-II. This instrument was subjected to the respective analyzes that determined that the test is valid and reliable. The results obtained indicate that Empowerment influences the learning achievements of the students in the sample. The existence of correlations between each of the dimensions of Empowerment with Learning Achievements was also verified. Therefore, it is recommended to strengthen this tool.